Hubungan Terpaan Informasi Promosi Penjualan Dan Citra Merek Wuling Motor Terhadap Minat Beli Konsumen - Daffa Argy Pradiptha; Djoko Setyabudi (Interaksi Online, 2020)
The automotive industry in Indonesia is very diverse, but currently dominated by industries from Japan, one of the best-selling sales is Toyota. This Japanese brand is very popular with Indonesian people. The community chooses four-wheeled vehicles that are functional, of good quality and of course at a friendly price. This automotive manufacturer from Japan has dominated the Indonesian automotive market for a long time. Wuling motors from China began to enter the Indonesian market three years ago. With the habits and beliefs of most Indonesian people choose a vehicle from Japan whether the Chinese manufacturer is able to compete or not. Therefore the researcher wants to find out whether promotion and brand image can influence buying interest. The purpose of this study is to find out the relationship between sales promotion and Wuling Motors brand image to consumer buying interest. The theory used by the writer is Cognitive Response Theory and Information Theory. This research is a quantitative research with explanatory type. This study uses non probability sampling techniques. With a total sample of 61 people aged 12 - 65 years from Instagram WulingMotorsId.Based on hypothesis testing conducted using Kendall's Tau-b correlation analysis, it shows that; First, there is a positive relationship between exposure to sales promotion information with consumer buying interest with a significance value of 0,000 and a correlation coefficient of 0.387. The higher the exposure to sales promotion information, the higher consumer buying interest, and vice versa. Second, there is a positive relationship between Wuling Motors brand image variables with consumer buying interest with a significance value of 0.031 and a correlation coefficient of 0.220. The higher the Wuling Motors brand image, the higher consumer buying interest, and vice versa.